Tooth Loss in Adults: A Survey of Reasons and Patterns in the Eastern Province of Aljabal Al-Akhder–Libya - Farag, Muna; Fathalla Benghsheer, Hala (Libyan Journal of Dentistry, 2023)
Aim: This study aimed to investigate the reasons and patterns of tooth extraction among adults in the eastern province of Libya. Methods: A cross-sectional study was carried out in three cities in Aljabal Al-Akhder in the east of Libya. A convenience sample was recruited from Libyan adult patients who underwent teeth extractions in dental practices in Albida, Goba and Derna from January 2022 to December 2022. The reasons and patterns for tooth extraction were collected using a form and it is categorized into: caries, periodontal diseases, orthodontic treatment, prosthetic treatment, impaction, trauma, and other reasons. Collected data were analyzed using SPSS software, the significance level was set at P value 0.05. Results: The study included data from 1000 patients, of whom 55.7% were females, and the mean age was 28 years (SD = 13.8). The most commonly reported reason for tooth extraction was dental caries (59.2%), followed by severe periodontitis (14,1%), tooth impaction (8,2%), prosthodontics reason (4.8%), and failed RCT (4.6%). The most common tooth extracted was the first molar (27.1%), followed by the third molar (19.2%) and second molar (15.3%). The least extracted teeth, other than retained primary teeth, were canine (1.7%) and central incisors (2.5%). Conclusion: Dental caries and periodontal diseases are the main causes of tooth loss among Libyan adults in Aljabal Al-Akhder. Molar teeth were the most commonly extracted teeth. Measures should be directed toward the prevention and early treatment of oral conditions to reduce teeth extractions and improve the oral health related quality of life.